Asymmetric Synthesis of P-Chiral Diphosphines. Steric Effects on the Palladium-Complex-Promoted Asymmetric Diels-Alder Reaction between a Dimethylphenylphosphole and (E/Z)-Methyl-Substituted Diphenylvinylphosphines. - Aw, B; Hor, T; Selvaratnam, S; Mok, K; White, A; Williams, D; Rees, N; McFarlane, W; Leung, P (1997)
The organopalladium complex containing ortho-metalated (S)-(1-(dimethylamino)ethyl)naphthalene as the chiral auxiliary has been used successfully to promote the asymmetric [4+2] Diels-Alder reactions between 1-phenyl-3,4-dimethylphosphole and the following coordinated dienophiles: (a) diphenylvinylphosphine; (b) (E)-diphenyl-1-propenylphosphine; (c) (Z)-diphenyl-1-propenylphosphine. Reaction a generates three carbon and one phosphorus stereogenic centers while reactions b and c each produce four carbon and one phosphorus chiral centers. In dichloromethane, all three reactions proceeded smoothly at room temperature giving the corresponding rigid diphosphines in high yields. Under similar reaction conditions, the reaction times observed for reactions a-c are 2, 3, and 50 h, respectively. Two-dimensional ROESY NMR studies confirmed that the prolonged reaction time required for reaction c is due to several major repulsive interactions between the chiral naphthylamine auxiliary and the (Z)-methyl-substituted vinylphosphine in the transition state. Nevertheless, all three reactions gave the corresponding rigid diphosphine in high yields. The absolute stereochemistries of the three bidentate phosphine ligands that were produced from the cycloaddition reactions have been assigned by 2D ROESY NMR spectroscopy. These diphosphines are powerful sequesterers of group 8 metals although they are highly air-sensitive in the free ligand form. The coordination chemistry and the absolute stereochemistry of the optically active complex [1alpha,4alpha,5alpha(S),6alpha(S),7R]-dichloro[5-(diphenylphosphino)-2,3,6-trimethy-7-phenyl-7-phosphabicyclo[2.2.1]-hept-2-ene-P(5)(),P(7)()]palladium(II) has been studied by single-crystal X-ray analysis. Crystal structure data: C(27)H(28)Cl(2)P(2)Pd, M(r) = 591.7; triclinic; space group P1; a = 8.643(3), b = 9.044(6), c = 9.058(4) Å; alpha = 102.75(4) degrees, beta = 108.59(2) degrees, gamma = 97.82(3) degrees; V = 638.0(5) Å(3); Z = 1; R(1) = 0.036.